Sleep quality and chronotype of Portuguese school-aged children - Gomes, A. M. (2021)
Is the perception of school-aged children and parents about the children’s sleep quality and chronotype consistent with their real sleep quality and effective chronotype? The research questions for this study were 1) Do children's sleep perceptions and chronotype differ from real sleep quality and chronotype? 2) Are there differences in sleep quality between genders? 3) What will be the effective quality of sleep and chronotype? The purpose of the study was to analyse the perceptions of children and parents about the children’s sleep quality and chronotype and compare them with effective sleep quality and chronotype, to study sleep quality and chronotype considering gender, and to analyse the perceptions of Portuguese parents about children’s sleep in a migrant context. The research method was a cross-sectional study, quantitative methodology. The data from three questionnaires were analysed with regard to the three study aims: the Pittsburgh Sleep Quality Index (PSQI) (n=1109 children), the Children’s Sleep Habits Questionnaire (CSHQ) (n=883 parents), and the Children's Chronotype Questionnaire (CCTQ) (n=58 parents, Portuguese emigrants in Luxembourg). The samples were collected from 8 Portuguese schools and 2 Luxembourg schools. The PSQI showed high sleep quality, which contradicts the results for CSHQ. Children from state schools (n=538) revealed higher diurnal dysfunction levels compared to the children from private schools (n=571). Females showed best sleep latency and duration. The CSHQ presented general negative sleep quality. The CCTQ demonstrated that parents’ perceptions did not fit with the effective children’s chronotype. The children's perception showed a wellbalanced sleep quality but the results revealed a high incidence of sleep disturbance. There were no statistical differences for gender. Portuguese emigrant parents revealed low awareness of their children’s chronotype and there was significant contrast between parents’ perceptions and the real chronotype of children.